HUBUNGAN GAYA KEPEMIMPINAN DEMOKRATIS KEPALA RUANGAN DENGAN MOTIVASI KERJA PERAWAT EKSEKUTIF RUANG RAWAT INAP ANAK DAN BLUD PICU RSUD DR. H. YULIDDIN TANDANG TAPAKTUAN - Irwan, Syam; Rahmi, Cut; Yulissasman, Yulissasman; Lizam, T. Cut; Rasima, Rasima (Jurnal Media Informatika, 2024)
Background: work motivation is a condition or energy that moves employees who are directed or aimed at achieving the company's organizational goals. It is the employee's pro and positive mental attitude towards the work situation that strengthens their work motivation to achieve maximum performance. The emergence of work motivation in a person is also influenced by the leader who is a role model for his subordinates in accordance with the understanding that leadership is a process of influencing other people in achieving goals. Objective: to analyze the relationship between the Democratic Leadership Style of the Room Head and the Work Motivation of Executive Nurses in Children's Inpatient Rooms and PICU BLUD RSUD dr. H. Yuliddian Away Tapaktuan Method: The design of this research is correlation research, namely research that connects one variable with another variable, then statistical testing is carried out or also known as a correlation test which will produce a correlation coefficient using a cross sectional study approach, namely a form of research on a sample of 30 people. Research Results: with a P value of 0.000, it means H0 or there is a visible relationship between the type of democratic leadership of the head of the pediatric inpatient room and PICU with motivation for the work of implementing nurses in the inpatient room and PICU BLUD RSUD dr H Yuliddin Away Tapaktuan. Conclusion: a significant P value of 0.000 (α=0.05) was obtained, so the hypothesis was accepted. Suggestion: the results of this research can provide input to service institutions for all nurses to increase work motivation, namely by having a democratic type of leadership